The role of communication on an experimental market for tradable development rights - Till Proeger; Lukas Meub; Kilian Bizer (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2016)
Tradable development rights (TDR) are discussed as a means of containing urban sprawl in numerous countries. Despite its theoretical superiority in ensuring an efficient redistribution of planning rights, its applicability is concerned with several open questions and potential problems. Introducing a novel experimental setting, we simulate a cap & trade TDR scheme and investigate the effects of communication, an aspect typically assumed to be irrelevant by theory. We consider communication among individual participants competing in a TDR system and team decision-making facilitated by face-to-face communication. We find the system to be quite efficient, despite overshooting certificate prices particularly in the beginning for both initial issuance in auctions and the secondary market. Communication significantly reduces auction prices, leading to substantially less income redistribution from participants to the auctioneer. This effect is explained by participants' improved understanding of the cap & trade system when communicating; despite participants' attempts, they fail to establish collusion. Team decision-making is not only shown to reduce overshooting prices; moreover, it also improves the system's efficiency. These results are interpreted as emphasizing the efficiency and political feasibility of TDR schemes when including communication among its participants.
Keywords: C91; C92; D8; 330; cap & trade; collusion; communication; economic experiment; land consumption; tradable planning permits